2015
DOI: 10.1534/genetics.115.176495
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genetic Analysis of Paralogous Terminal Septin Subunits Shs1 and Cdc11 inSaccharomyces cerevisiae

Abstract: Septins are a family of GTP-binding proteins considered to be cytoskeletal elements because they self-assemble into filaments and other higher-order structures in vivo. In budding yeast, septins establish a diffusion barrier at the bud neck between a mother and daughter cell, promote membrane curvature there, and serve as a scaffold to recruit other proteins to the site of cytokinesis. However, the mechanism by which any septin engages a partner protein has been unclear. The two most related and recently evolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
77
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(105 citation statements)
references
References 151 publications
(173 reference statements)
13
77
1
14
Order By: Relevance
“…Consistent with other evidence that the C-terminal end of Bni5 is required for its function (Finnigan et al ., 2015a), Bni5-β11 interacted exclusively with N-terminally β10-tagged Cdc11 and Shs1 and no other septin. In agreement with structure predictions that Bni5 is an elongated, highly α-helical protein, β10-Bni5 had a longer “reach,” yielding a readily detectable fluorescence signal with every C-terminally β11-tagged septin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other evidence that the C-terminal end of Bni5 is required for its function (Finnigan et al ., 2015a), Bni5-β11 interacted exclusively with N-terminally β10-tagged Cdc11 and Shs1 and no other septin. In agreement with structure predictions that Bni5 is an elongated, highly α-helical protein, β10-Bni5 had a longer “reach,” yielding a readily detectable fluorescence signal with every C-terminally β11-tagged septin.…”
Section: Discussionsupporting
confidence: 92%
“…These basic residues are believed to mediate interaction with phosphatidylinositol-4,5- bis -phosphate (PtdIns4,5P 2 ) on the inner leaflet of the PM (Bertin et al ., 2010) and are required for the full in vivo function of these septins (Finnigan et al ., 2015b). Thus access to a tag placed at the N-terminus of either of these two septins may be limited, resulting in a weaker signal in this assay format.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions between, for example, Cdc12-Cdc3, Cdc10-Cdc10 and Cdc11-Cdc11 at the so-called 'NC' interface are essential (Beise and Trimble, 2011;Sirajuddin et al, 2007). The terminal subunit Cdc11 can be replaced by an alternative septin subunit Shs1, resulting in the formation of alternative heterooctamers (Booth et al, 2015;Finnigan et al, 2015;Garcia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of GFP and other genetically encoding fluorescent protein tags to follow protein dynamics in live cells in real time revealed further that septin organization undergoes dramatic changes during cell cycle progression. Septins first accumulate as a patch at the incipient site of bud emergence that rapidly resolves into a filamentous ring (Kozubowski et al, 2005; Okada et al, 2013), which then expands, concomitant with bud growth, into an hourglass-shaped tube or collar composed of at least 30–40 gyres of circumferential filaments at the bud neck (Byers and Goetsch, 1976; McMurray et al, 2011; Finnigan et al, 2015b; Patasi et al, 2015). At the onset of cytokinesis, the collar splits into two fllamentous bands of roughly equal size with a prominent gap in between (Dobbelaere et al, 2003; Dobbelaere and Barral, 2004) wherein factors needed for actomyosin contractile ring assembly and new plasma membrane (PM) and cell wall (CW) synthesis accumulate (Bi et al, 1998; Nishihama et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro the former can associate end-to-end into paired filaments in low-salt solution and into sheets of paired filaments on the surface of a lipid monolayer containing phosphatidylinositol-4,5- bis phosphate (Bertin et al, 2010). Mutagenesis studies have shown that the residues needed for these characteristic in vitro behaviors are also essential for viability in vivo (Bertin et al, 2008; McMurray et al, 2011; Finnigan et al, 2015b). The Shs1-containing hetero-octamers associate laterally in a staggered fashion, rather than end-on-end, forming curved bundles, rings, and bird's nest-like structures in vitro (Garcia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%